Diaspora linkages benefit both sides: a single partnership experience - Beverley Kramer; Roy Zent (Taylor & Francis Group, 2019)
The emigration of physicians and scientists from resource-constrained countries decreases the country's ability to undertake research. Re-establishing research environments and increasing capacity reduced by these losses are important, particularly in the health sciences. One mechanism for re-establishing strong health sciences research is the introduction of an Alumni Diaspora Fellowship Programme. We define the beneficial effects of a successful single partnership in an Alumni Diaspora Programme. This Host/Alumnus collaboration demonstrates that bi-directional advantages have accrued for both the Host Institution situated in a resource-constrained country and the Alumni's Institution, located in a high-income country. In addition to expanding research in the resource-constrained country, collaborations expanded to other faculty beyond the Alumnus in the sending Institution, in multiple fields including those not readily available in the high-income country (HIV, TB, malaria). The environment at the host Institution in the resource-constrained country has been enriched by increased research publications, training of young scholars (over 200 trained in manuscript and grant application writing), and substantial advances in biomedical informatics. There has been considerable knowledge exchange and development between both Institutions, showing that 'brain circulation' and Diaspora Programmes are valuable strategies for expanding research.